2014
DOI: 10.1002/art.38748
|View full text |Cite
|
Sign up to set email alerts
|

DNA Microarray Analysis of Labial Salivary Glands in IgG4‐Related Disease: Comparison With Sjögren's Syndrome

Abstract: Objective. To compare gene expression in labial salivary glands (LSGs) from patients with IgG4-related disease with that in LSGs from patients with Sjögren's syndrome (SS).Methods. Gene expression was analyzed by DNA microarray in LSG samples from 5 patients with IgG4-related disease, 5 SS patients, and 3 healthy controls. Genes differentially expressed in IgG4-related disease and SS were identified, and gene annotation enrichment analysis of these differentially expressed genes was performed using Gene Ontolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 34 publications
6
41
0
Order By: Relevance
“…We showed that the up-regulated sets of DEGs in patients with SS-encoded proteins that function in antigen processing and presentation of peptide antigen in the gene-annotation enrichment analysis, as we have reported previously [7]. We showed that the up-regulated sets of DEGs in patients with SS-encoded proteins that function in antigen processing and presentation of peptide antigen in the gene-annotation enrichment analysis, as we have reported previously [7].…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…We showed that the up-regulated sets of DEGs in patients with SS-encoded proteins that function in antigen processing and presentation of peptide antigen in the gene-annotation enrichment analysis, as we have reported previously [7]. We showed that the up-regulated sets of DEGs in patients with SS-encoded proteins that function in antigen processing and presentation of peptide antigen in the gene-annotation enrichment analysis, as we have reported previously [7].…”
Section: Discussionsupporting
confidence: 83%
“…In SS patients, 1785 up-regulated probe sets (corresponding to 1320 up-regulated genes) and 1771 down-regulated probe sets (corresponding to 1321 down-regulated genes) were identified as DEGs (FDR < 0Á05, compared with IgG4-RD) (Supporting information, Table S1). Geneannotation enrichment analysis by the Web tool DAVID and QuickGO showed that significantly enriched Gene Ontology (GO) terms (FDR-corrected P-value < 0Á0001) found in highly expressed probe sets in SS compared with IgG4-RD included protein glycosylation, immune response, antigen processing and presentation of peptide antigen via major histocompatibility complex (MHC) class I, Golgi vesicle transport, co-translational protein targeting to membrane, endoplasmic reticulum (ER) unfolded protein response and response to virus, as reported previously by our group [7]. In contrast, gene-annotation enrichment analysis by GO annotation showed that the down-regulated set of DEGs in SS encoded proteins that function in wound healing, response to inorganic substance, skeletal system development, muscle organ development, heart development, angiogenesis, cell morphogenesis involved in cDNA microarray identifies NR4A2 in SS V C 2017 British Society for Immunology, Clinical and Experimental Immunology, 190: 96-109 differentiation, cell projection organization, muscle contraction, extracellular matrix organization, actin cytoskeleton organization, cell-matrix adhesion, regulation of cell migration, regulation of cell-substrate adhesion, positive regulation of cell adhesion, regulation of cell proliferation, enzyme linked receptor protein signalling pathway, regulation of inflammatory response and translational elongation, as shown in our previous report [7].…”
Section: Cdna Microarray Analysissupporting
confidence: 74%
See 2 more Smart Citations
“…The roles of chemotactic factors in the immunopathology of IgG4-RD are poorly understood, with only less than a dozen chemotactic factors known to be upregulated (e.g., CXCL13, CCL18, and CCR4) [114,115]. A critical question is which chemotactic factors are involved in creating a milieu rich in Th2 and Tregs.…”
Section: Chemokines and Chemokine Receptorsmentioning
confidence: 99%